Does Parenting Perfectionism Ironically Increase Violent Behaviors from Parent towards Children? - Alice Schittek; Isabelle Roskam; Moira Mikolajczak (MDPI AG, 2023)
Background: Past research has shown that perfectionistic strivings (PS) and perfectionistic concerns (PC) in the parenting domain are associated with an increase in parental burnout (PB), and that PB causally increases violence towards one's offspring. One may therefore wonder whether parenting perfectionism may ironically increase violence towards one's offspring. Objective: To the best of our knowledge, no study has ever investigated whether perfectionism (PS and PC) predicts violence towards one's offspring, or whether PB could explain this link. In the current pre-registered cross-lagged study, we hypothesized that an increase in PS and PC would lead to an increase in violence via an increase in PB. Method: 228 participants responded to a longitudinal online survey, with three measurement occasions spaced 2 months apart. Results: Contrary to expectations, cross-lagged path models revealed that violence towards the offspring prospectively predicted an increase in PS and PC. Mediation models showed that PB was not a significant mediator. Results of all models did not change when controlling for social desirability. Conclusion: The present study shows that violence towards the offspring increases the risk of PS and PC in parents. Results are discussed in light of the feeling of guilt experienced by parents. Implications: Current worries that parenting perfectionism may paradoxically increase violence appear to be unwarranted at this stage. Moreover, correlation is not causation; thus, emphasizing caution before coming to clinically and societally relevant conclusions in cross-sectional studies. Thus, the PB and child maltreatment literature should slowly shift to using more longitudinal and causal designs.